2009
DOI: 10.1590/s0100-40422009000600008
|View full text |Cite
|
Sign up to set email alerts
|

Síntese e avaliação da atividade antimicrobiana de novas 4-tiazolidinonas obtidas a partir de formilpiridina tiossemicarbazonas

Abstract: , 50670-901 Recife -PE, BrasilRecebido em 14/5/08; aceito em 13/2/09; publicado na web em 3/7/09 SYNTHESIS AND ANTIMICROBIAL ACTIVITIES OF NEW 4-THIAZOLIDONES DERIVED FROM FORMIPYRIDINE THIOSEMICARBAZONES. Twelve novel 4-thiazolidinone derivatives (2a-l) have been synthesized by reacting formilpyridine thiosemicarbazones (1a-l) and anhydride maleic in toluene. Their chemical structures were confirmed by IR, 1 H and 13 C NMR. The new compounds were submitted to in vitro evaluation against pathogenic Gram-positi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In turn, recent work in our research group showed that some 4-thiazolidinone derivatives (b, Figure 1) obtained from formilpyridine thiosemicarbazones possess considerable antimicrobial activity against Micrococcus luteus, Mycobacterium phlei, Mycobacterium smegmatis, Mycobacterium tuberculosis, Malassezia furfur and Candida albicans. 7 On the other hand, Zhou et al 8 identified ten cytoselective compounds from 372 thiazolidinone analogues (c, Figure 1) by applying iterative library approaches. These compounds selectively killed both non-small cell lung cancer cell line H460 and its paclitaxel-resistant variant H460taxR at an IC 50 between 0.21 and 2.93 μM while showing much less toxicity to normal human fibroblasts at concentrations up to 195 μM.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, recent work in our research group showed that some 4-thiazolidinone derivatives (b, Figure 1) obtained from formilpyridine thiosemicarbazones possess considerable antimicrobial activity against Micrococcus luteus, Mycobacterium phlei, Mycobacterium smegmatis, Mycobacterium tuberculosis, Malassezia furfur and Candida albicans. 7 On the other hand, Zhou et al 8 identified ten cytoselective compounds from 372 thiazolidinone analogues (c, Figure 1) by applying iterative library approaches. These compounds selectively killed both non-small cell lung cancer cell line H460 and its paclitaxel-resistant variant H460taxR at an IC 50 between 0.21 and 2.93 μM while showing much less toxicity to normal human fibroblasts at concentrations up to 195 μM.…”
Section: Introductionmentioning
confidence: 99%